The effects of physical exercise on college students’ academic achievement: the chain mediating role of emotional intelligence and academic mood - Jiang, Yong; Ren, Siyu (Frontiers in Psychology, 2025)
IntroductionThis study aims to explore the mechanism of physical exercise’s influence on the academic achievement of contemporary college students, and focuses on the mediating role of emotional intelligence and academic mood in it.MethodsThrough a large-scale questionnaire survey of 540 college students, a chain mediation model was constructed, and the mediating effects of emotional intelligence and academic mood were examined and analyzed using structural equation modeling and Bootstrap method.Results(1) Physical exercise can positively predict college students’ academic achievement; (2) Physical exercise can mediate college students’ academic achievement through emotional intelligence and academic mood, respectively; (3) Physical exercise can affect college students’ academic achievement through emotional intelligence and academic mood in a chain. Three pathways of mediating effects: physical exercise → emotional intelligence → academic achievement (path 1), physical exercise → academic mood → academic achievement (path 2), and physical exercise → emotional intelligence → academic mood → academic achievement (path 3).DiscussionThe results of the study show that physical exercise not only directly promotes academic achievement, but also indirectly affects academic achievement through the mediating effect of emotional intelligence and academic mood. This study provides empirical evidence for an in-depth understanding of the relationship between physical exercise and academic achievement, and provides theoretical references for the synergistic promotion of college students’ mental health and academic development.